Tuberization in Potato Involves a Switch from Apoplastic to Symplastic Phloem Unloading - Viola, Roberto (American Society of Plant Physiologists, 2001)
Phloem unloading was studied in potato plants in real time during the early stages of tuberization using carboxyfluorescein (CF) as a phloem-mobile tracer, and the unloading pattern was compared with autoradiography of tubers that had transported (14)C assimilates. In stolons undergoing extension growth, apoplastic phloem unloading predominated. However, during the first visible signs of tuberization, a transition occurred from apoplastic to symplastic transport, and both CF and (14)C assimilates subsequently followed identical patterns of phloem unloading. It is suggested that the switch to symplastic sucrose unloading may be responsible for the upregulation of several genes involved in sucrose metabolism. A detailed analysis of sugar levels and (14)C sugar partitioning in tuberizing stolons revealed a distinct difference between the apical region of the tuber and the subapical region. Analysis of invertase activity in nontuberizing and tuberizing stolons revealed a marked decline in soluble invertase in the subapical region of swelling stolons, consistent with the switch from apoplastic to symplastic unloading. However, cell wall–bound invertase activity remained high in the apical 1 to 2 mm of tuberizing stolons. Histochemical analysis of potato lines transformed with the promoter of an apoplastic invertase gene (invGE) linked to a reporter gene also revealed discrete gene expression in the apical bud region. Evidence is presented that the apical and lateral tuber buds function as isolated domains with respect to sucrose unloading and metabolism.